RASIONALITAS NILAI DALAM PELESTARIAN BUDAYA MELAYU MELALUI LITERASI DIGITAL - Herlina; Indah Solehati; Resti (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This research examines the practice of digitization of Malay cultural heritage by communities in Palembang, through the perspective of Max Weber's value rationality (Wertrationalität). In the context of globalization and digital transformation, digitization is not solely seen as a technical preservation effort, but also as a way to express cultural values and strengthen collective identity. This research aims to: 1) Examine the value-based motivation in the practice of digitization of Malay cultural heritage. 2) Analyse the forms of action that reflect value rationality in cultural preservation through digital media; 3) Explain the relationship between digital literacy and commitment to Malay cultural preservation. This research uses a qualitative approach with a case study design, involving in-depth interviews and documentation of cultural digitization activities such as Jawi manuscripts, poems, and oral traditions. The results show that acts of cultural preservation are carried out based on a commitment to moral values and ancestral heritage, not for material gain. Digitalization is understood as a means of affirming Malay identity and transmitting cultural values to the younger generation through digital media. In addition, the digital literacy that develops in the cultural preservation community reflects a critical understanding of cultural content and meaning, not just technical skills. The findings enrich interdisciplinary studies between cultural sociology, information studies, and digital literacy and offer strategic recommendations for cultural actors and digital platform developers in designing value-based cultural preservation.